Hygienic and efficient steam tools for increased productivity of Tape craftsmen in Tanjung Sari village, Medan Selayang district (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Indonesia is an agrarian country, the lives of most of its people work in the field of agricultural products. The raw materials produced by the agricultural industry include cassava tubers. Cassava tubers are fermented with the help of yeast sown on the surface of yams that have been steamed to become a sweet tape. The problem felt by partners is the use of steaming tools for 5 hours for cassava capacity of 800 kg per day has the potential to cause steaming devices to leak and make production capacity not achieved. There was also a problem with stoves that were often dirty, resulting in red and uneven flames, which caused the steam process to take longer and waste energy. The steamer stand used so far is a brick that has the potential to make the steaming tool spill over and overturn and fly dust (unhygienic). In this case, we need a touch of technology for the steaming process to ensure the smooth production process continues to run according to production targets and is able to accelerate the process of steaming tape and hygienic. The application of appropriate technology with a steaming device with aluminum material with a thickness of 1 millimeter following a two-cast cast iron stove along with its iron stand is considered appropriate, efficient, and does not increase production costs that are too high to ensure a smooth production process. The target and output of this activity is the achievement of a production capacity of 800 kg per day and it is expected that the processing time for steaming cassava is shorter by the use of appropriate technology, a cast iron stove with two faucets and a metal stand.